Workplace Psychological Aggression, Job Stress, and Vigor: A Test of Longitudinal Effects - Malik, Omer Farooq (Journal of interpersonal violence, 2021)
The purpose of this research was to examine the relationships between supervisor- and customer-initiated psychological aggression and vigor across time, and to determine the mediating role of job stress in these relationships. We also investigated the potential for differential impacts of supervisor and customer aggression on our outcome variables. A two-wave longitudinal study was conducted with a time lag of 6 months. The study sample consisted of 215 branch office employees of five large commercial banks situated in Islamabad, Pakistan. Data were collected using a self-administered questionnaire and analyzed using covariance-based structural equation modeling (CB-SEM). It was found that Time 1 supervisor and customer aggression were negatively related to Time 2 vigor, and these relationships were partially mediated by job stress. Contrary to our expectations, however, we found no significant differences between Time 1 supervisor and customer aggression in relation to Time 2 job stress and Time 2 vigor. The theoretical and practical implications of these findings are discussed. We extended research on multifoci approach to workplace aggression and empirically examined the direct and mediated effects of supervisor- and customer-initiated psychological aggression on vigor.